2010
DOI: 10.1017/s0022215110002082
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with idiopathic sudden hearing loss: role of vestibular assessment

Abstract: In patients with idiopathic sudden hearing loss, the extent of the inner ear lesion tends to correlate with the severity of cochlear damage. Vestibular assessment may be valuable in predicting the final outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Vertigo is a widely reported negative predictive factor for hearing recovery in ISSNHL . The extent of the labyrinthine lesion might correlate with the severity of cochlear damage, and the likelihood of hearing recovery tends to reduce as the degree of labyrinthine involvement increases . In children, the incidence of vertigo in SSHNL ranges from 17% to 50%, and the presence of vertigo is not always indicative of poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertigo is a widely reported negative predictive factor for hearing recovery in ISSNHL . The extent of the labyrinthine lesion might correlate with the severity of cochlear damage, and the likelihood of hearing recovery tends to reduce as the degree of labyrinthine involvement increases . In children, the incidence of vertigo in SSHNL ranges from 17% to 50%, and the presence of vertigo is not always indicative of poor prognosis .…”
Section: Discussionmentioning
confidence: 99%
“…10 The extent of the labyrinthine lesion might correlate with the severity of cochlear damage, and the likelihood of hearing recovery tends to reduce as the degree of labyrinthine involvement increases. 24 In children, the incidence of vertigo in SSHNL ranges from 17% to 50%, 17,25 and the presence of vertigo is not always indicative of poor prognosis. 23 The current study found that vertigo was not a factor in hearing recovery in pediatric ISSNHL, a result that implies that ISSNHL has a different etiology in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there had no significant differences on above clinic features among 5 age groups. It has been reported in many studies that there could be a particular percentage of otolithic involvement while cochlear impairment in patients with SSHL [9]-[11] [17]. As objective testing programmes, cVEMP and oVEMP tests were employed to assess saccular and utricular fuction by researchers.…”
Section: Discussionmentioning
confidence: 99%
“…[1,4,5,12] Some reports have indicated that abnormal caloric test results in SSNHL patients may be of negative prognostic value [1,13], whereas other studies have shown that the results of caloric testing may not be predictive of SSNHL [4,5,14]. Furthermore, several recent studies have included the VEMP test in the evaluation of patients with SSNHL, for whom abnormal results of vestibular examinations were associated with profound hearing loss [6,15]. 5 The present study aimed to determine the association of VFT results with the initial disease severity and prognosis of hearing outcomes in SSNHL patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 The present study aimed to determine the association of VFT results with the initial disease severity and prognosis of hearing outcomes in SSNHL patients. 6…”
Section: Introductionmentioning
confidence: 99%